The effector of hedgehog signaling, the transcription factor GLI1: novel regulatory mechanisms and role in tamoxifen treatment (2017)
In Chapter I, we describe the characterization of an RNA transcript from the antisense strand of the GLI1 gene, termed GLI1AS, with no potential to code for a long protein, which acts as a negative regulator of GLI1 expression. We provide evidence for capping and polyadenylation of this antisense RNA, suggesting that it is processed similarly to a typical mRNA, even though it lacks the potential to code a protein. Additionally, our data show that GLI1 mRNA expression is higher than GLI1AS across all samples examined, consistent with the results reported for most antisense transcripts with regulatory roles on the corresponding sense gene. Chromatin immunoprecipitation assays supported the notion that GLI1AS acts as an epigenetic modifier, which elicits negative feedback on GLI1 expression via local chromatin remodeling, observations that were in-line with cellular proliferation and chick chorioallantoic membrane (CAM) tumor assays. In Chapter 2, we present in vitro data using a number of different breast cancer cell lines, demonstrating the modulatory effect of tamoxifen (TAM) on cellular proliferation and expression of HH signaling components, in particular GLI1. Our results show that cell lines that express nuclear GLI1 staining after TAM treatment exhibit an increase in cell proliferation compared to control, GLI1 negative cells. These findings could indicate that the HH signaling pathway can be activated by TAM in breast cancer cells, eliciting cellular growth.